Management of Unicistic Ameloblastoma in a Young Patient: Reducing Social Consequences - Mendes, Bruno Coelho [UNESP]; Maia, Rafael Alberto Dos Santos; Santos, Anderson Maikon de Souza [UNESP]; Moura, Kaline da Silva; Araújo-Filho, Nilton Pires de; Aburad, Arlindo Tadeu Teixeira; Faverani, Leonardo Perez [UNESP]; Borba, Alexandre Meireles (My University, 2021)
ABSTRACT: Ameloblastoma is an odontogenic tumor of significant clinical relevance, aggressive and locally invasive. Although the posterior region of the mandible is more frequently affected, lesions observed in the maxilla should receive special attention due to the risk of expansion to the nasal, paranasal and orbital structures. This report shows a successful case of a maxillary ameloblastoma treated by combining therapies in a young patient. The treatment strategy adopted to reduce and redefine the lesion dimensions enabled enucleation in a safe way, without destruction of adjacent noble structures. It also allowed complementary approach with peripheral ostectomy and sclerosing agent, efficiently, without evidence of recurrence or complications after 2 years.